Factor XII (Hageman) Levels in Women with Recurrent Pregnancy Loss. (20th November 2014) - Ozgu-Erdinc, A. Seval; Togrul, Cihan; Aktulay, Ayla; Buyukkagnici, Umran; Yapar Eyi, Elif Gul; Erkaya, Salim
Abstract : Objective . To evaluate factor XII levels in women with recurrent pregnancy loss (RPL) in a tertiary referral hospital. Methods . Women who were referred to our hospital for two consecutive abortions or three abortions in between 2007 and 2013 were included in this retrospective observational study. Women were further grouped according to factor XII levels, as <60% and ≥60%. Results . Mean factor XII level was 109.1 ± 35.7% (range: 9–200). Ninety-three (7.4%) women had factor XII levels < 60%. Mean factor XII level was 44.8 ± 13.1, and levels ranged between 9 and 60 in this group. Only one woman had factor XII level < 10 %. Remaining 1164 (92.6%) women had factor XII levels ≥ 60%. Mean factor XII level was 114.3 ± 31.7, and levels ranged between 60.3 and 200 in this group, while 1015 (72.4%) women had factor XII levels within the normal range (60%–150% [100% = 30  μ g/mL]). Conclusion . Decreased activity of F-XII was diagnosed in 7.4% of women with RPL. We concluded factor XII deficiency that might be a rare but significant factor for RPL, and should be evaluated in women who are investigated for recurrent pregnancy loss.